Severe Thrombocytopenia Secondary to Severe Iron Deficiency Anemia due to Menorrhagia - Tyler E. Russeth; Amanda Luong; Mandi Liu; Mihir Shah; Nicole Desai (Case Reports in Hematology)
Thrombocytosis is commonly seen in patients with iron deficiency anemia and often normalizes following iron supplementation. Thrombocytopenia with iron deficiency anemia is a less common occurrence that can be seen in severe cases. This phenomenon is well documented in the pediatric population secondary to nutritional deficiency but is underreported in the adult population. Similarly, thrombocytopenia resolves following iron supplementation but the mechanism behind this and why select patients are affected is not well understood. This case report describes a young woman with menorrhagia who was found to have iron deficiency anemia and severe thrombocytopenia with resolution following intravenous iron.